Discourse Analysis - Khalid Saifullah (Linguistics and Literature Review, 2016)
The present study aims at analyzing the discourse of Sufi poetry, a prominent genre of Sufi Literature. Sufi poets have been publicizing Sufism and their philosophy through poetry. Text and language is central to Sufi literature therefore Sufi poets use poetic language to mesmerize the hearts of people. In this study thematic discourse analysis of Sufi poetry is conducted in qualitative research paradigm whereas Post-structuralism is used as theoretical framework epistemologically. Textual data in form of poetry verses is collected purposively from online resources. The study concludes that poetry of two Sufi poets, Bulleh Shah and Rumi holds common themes of universal love, purification of soul and humility.